(untitled) - Prof. Dr. Umbreen Javaid, Prof. Dr. M. Iqbal Chawla (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The objective of the current study is to find out the factors of peace building and countering violent extremism in Pakistan. In the modern day world violent religious extremism is very much prevalent and the issue is even worse in Pakistan where numerous religious and ethnic minorities are present. For this purpose qualitative inquiry followed by secondary data analysis technique has been adopted by the researcher. For this purpose significant empirical literature from research journal, reports and books were analyzed. The findings of the study illustrate the collective national identity along with social process and cultural rejuvenation are vital in restoring the peace and countering violent religious extremism. In addition to that the role of media and social institutions is very handy owing to their wide range approach and scope.